2002
DOI: 10.1542/peds.109.3.498
|View full text |Cite
|
Sign up to set email alerts
|

Seven-Year Follow-up of Vaccine Response in Extremely Premature Infants

Abstract: At 7 years of age, PT children had lower antibody titers to many vaccine antigens than FT children. However, most PT children maintained antibody titers in the protective range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
1
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 26 publications
(30 reference statements)
1
24
1
4
Order By: Relevance
“…Apenas um quinto destes lactentes não soroconverteram de imediato e foram exatamente os nascidos de parto gemelar e pré-termo. A prematuridade e o baixo peso ao nascer provavelmente são os principais fatores que influenciaram negativamente na soroconversão pós-vacinal [22][23][24][25] . Entretanto, tais recém-nascidos, supostamente com imunidade inferior à dos demais, soroconverteram mais tarde, após a quarta dose de vacina, demonstrando terem sido válidas as suas imunizações, tanto quanto à profilaxia pós-exposição quanto à prevenção diante de possíveis exposições futuras.…”
Section: Discussionunclassified
“…Apenas um quinto destes lactentes não soroconverteram de imediato e foram exatamente os nascidos de parto gemelar e pré-termo. A prematuridade e o baixo peso ao nascer provavelmente são os principais fatores que influenciaram negativamente na soroconversão pós-vacinal [22][23][24][25] . Entretanto, tais recém-nascidos, supostamente com imunidade inferior à dos demais, soroconverteram mais tarde, após a quarta dose de vacina, demonstrando terem sido válidas as suas imunizações, tanto quanto à profilaxia pós-exposição quanto à prevenção diante de possíveis exposições futuras.…”
Section: Discussionunclassified
“…Kirmani et al [15] observed protective anti-PRP antibody titers (>1.0 µg/ml) lingering for 7 years in children vaccinated in early childhood; higher concentrations were presented in full-term infants than in preterm children. Similarly, Heath et al [11] examining anti-PRP antibody concentrations in preterm infants at 2, 5, 12, and 64 months of age, demonstrated that premature infants developed lower antibody concentrations than term infants following Hib conjugate vaccination but, despite this, they achieved very high levels of clinical protection.…”
Section: Discussionmentioning
confidence: 98%
“…10 Another concern with the first immunization at 2 months, regardless of their corrected age, is an inadequate antibody response after the vaccination. Different groups [11][12][13][14] analyzed the antibody response in premature babies and found over a longitudinal time lower antibody titres, but in most of them the antibody levels were in the protective range. Local reactions were rare, and training on the correct immunization technique is considered indispensable.…”
Section: Discussionmentioning
confidence: 99%